2017
DOI: 10.3892/ijo.2017.4120
|View full text |Cite
|
Sign up to set email alerts
|

Trophic and neurotrophic factors in human pituitary adenomas (Review)

Abstract: The pituitary gland is an organ that functionally connects the hypothalamus with the peripheral organs. The pituitary gland is an important regulator of body homeostasis during development, stress, and other processes. Pituitary adenomas are a group of tumors arising from the pituitary gland: they may be subdivided in functional or non-functional, depending on their hormonal activity. Some trophic and neurotrophic factors seem to play a key role in the development and maintenance of the pituitary function and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 157 publications
(161 reference statements)
0
10
0
Order By: Relevance
“…By investigating the invasion mechanism of tumors, it has been shown that tumor invasion is closely related to pituitary tumor transforming gene (PTTG), vascular endothelial growth factor (VEGF), and matrix metalloproteinases (MMPs). However, these markers cannot accurately predict tumor prognosis in clinical applications [8,9]. In the process of exploring novel therapies, molecular targeted therapy has been used for the treatment of tumors [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…By investigating the invasion mechanism of tumors, it has been shown that tumor invasion is closely related to pituitary tumor transforming gene (PTTG), vascular endothelial growth factor (VEGF), and matrix metalloproteinases (MMPs). However, these markers cannot accurately predict tumor prognosis in clinical applications [8,9]. In the process of exploring novel therapies, molecular targeted therapy has been used for the treatment of tumors [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of diagnostic and therapeutic methods, the 5-year survival rate of patients with secreting pituitary adenoma has increased in recent years (5,6). However, considering that the pathogenesis of this tumor is very complex (7,8), a clearer understanding of the process will be helpful for defining more effective diagnostic and therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…It is biologically plausible that FGF-2 may downregulate the expression of NCAM in PitNETs, taking into account that FGFs are implicated in many processes of pituitary homeostasis and pituitary tumourigenesis. [49][50][51][52][53][54][55][56] Intracellular signalling by NCAM and its physiological effects are mediated by FGF-receptors, [57][58][59] with previous studies reporting that activation of NCAM-mediated FGF-receptor-1 downstream signalling factors is involved in neurite outgrowth and tumour progression. 60,61 Indeed, downregulation of several adhesion molecules has been reported in different human cancers, which is at least partly the result of high levels of growth factors such as FGF within the local TME.…”
Section: Discussionmentioning
confidence: 99%